Statistics Self-Concept, Statistics Self Efficacy dan Statistic Anxiety Mahasiswa Non-Eksakta: Analisis Model Sequential Explanatory - Gazali, Muh; Mursyid, Mursyid (SAP (Susunan Artikel Pendidikan), 2024)
Statistic emerges concern for social science students. Especially those who do not have sufficient mathematical experience, so they tend to build a negative paradigm towards statistics. The aim of this study was to build an argument related to the statistical attitude of social science students towards statistics and the statistical learning process through the integration of quantitative data and qualitative data, then proposes several important points to build effective statistics learning for social science students. Sampling of the number of Islamic Religious Universities in Jambi Province and the number of students used non-probability sampling. So that 3 universities and 375 students of the Tarbiyah and Teacher Training Faculty were obtained who took the Education Statistics course in the 2021/2022 academic year. Dealing with the sequential explanatory model analysis, this study argued that high or low anxiety in understanding the material and anxiety in completing statistical tasks were influenced by statistics self-concept and statistical self-efficacy. Furthermore, several factors that cause low statistical self-concept and statistical self-efficacy and were followed by high statistics anxiety were math experience, online learning system, statistics teacher competence, and assignment of statistical tasks beyond normal limits.